2020
DOI: 10.1186/s12885-020-07201-9
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-based cytology for the detection of cervical intraepithelial lesions in Jimma town, Ethiopia

Abstract: Background: Cervical cancer is the second leading type of female cancer in Ethiopia. Screening for cervical cancer is primarily conducted using visual inspection with 5% acetic acid (VIA). Liquid-based cytology (LBC) is not yet widely used in Ethiopia. Method: Women aged 21-65 years were tested using LBC and VIA to detect cervical dysplasia. Logistic regression analysis was conducted to identify associated factors. Cohen's Kappa test was conducted to test agreement between LBC and VIA. Results: Forty-two perce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Liquid-based cytology has gradually replaced the traditional Pap smear in specimen collection and specimen preparation technology, and according to some studies, the positive detection rate of liquid-based cytology in squamous epithelial lesions and cervical cancer can reach 93% and 100%, respectively. However, the positive detection rates of traditional Pap smears in the above two cervical lesions are 77.80% and 90.90%, respectively [ 11 , 12 ]. The results of this study showed that the positive rate of liquid-based cytology test results increased with the increase of pathological grade.…”
Section: Related Workmentioning
confidence: 99%
“…Liquid-based cytology has gradually replaced the traditional Pap smear in specimen collection and specimen preparation technology, and according to some studies, the positive detection rate of liquid-based cytology in squamous epithelial lesions and cervical cancer can reach 93% and 100%, respectively. However, the positive detection rates of traditional Pap smears in the above two cervical lesions are 77.80% and 90.90%, respectively [ 11 , 12 ]. The results of this study showed that the positive rate of liquid-based cytology test results increased with the increase of pathological grade.…”
Section: Related Workmentioning
confidence: 99%
“…Ameya and his colleague from Hawassa, Ethiopia also reported exactly the same pattern matching our report [ 24 ]. A study in Jimma, Ethiopia also revealed that women above 50 years were more likely to have advanced cervical lesions [ 47 ]. A study in Ghana also revealed that 71% of the patients with cervical cancer were ≥50 years old [ 27 ], which is precisely in line with our report.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Ethiopia showed that, patients with cervical cancer were most often visited health facilities after a long time leading to advanced stages of the disease at time of diagnosis [ 47 , 48 ]. This might be due to poor awareness of the disease and the nature of the screening program in the country that is mainly by using VIA technique.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the second most common cancer in women in underdeveloped countries. In 2018, over 300,000 women died from cervical cancer and more than 85% of them occurred in third-world countries [ 19 ]. Screening and treatment of pre-cancer lesions in women beyond 30 years of age is the most cost-effective way to prevent cervical cancer.…”
Section: Discussionmentioning
confidence: 99%